Geology and geochemistry of the Macheng Algoma-type banded iron-formation, North China Craton: Constraints on mineralization events and genesis of high-grade iron ores. (1st December 2015) - Wu, Huaying; Niu, Xianglong; Zhang, Lianchang; Pirajno, Franco; Luo, Huabao; Qin, Feng; Cui, Minli; Wang, Changle; Qi, Min
Highlights: The Macheng iron deposit is an Algoma-type BIF, formed at ca. 2540 Ma. High-T hydrothermal fluids interacting with seawater in a back-arc basin setting. Supergene enrichment and migmatization produced high-grade ores. Abstract: The Macheng iron deposit is located in the eastern Hebei province of the North China Craton (NCC). It is hosted in Neoarchean metamorphic rocks of Baimiaozi formation in the Dantazi Group, consisting of biotite-leptynite, plagioclase-gneiss, plagioclase-amphibolite, migmatite, migmatitic granite and quartz schist. Geochemical analyses of the host biotite leptynite and plagioclase amphibolites show that their protoliths are both volcanics, inferred to be trachytic basalt and basaltic andesite, respectively. Based on the geochemical signature of the host rocks, together with geology of the iron deposit, it is inferred that the Macheng BIF is an Algoma-type iron exhalative formation, formed in an arc-related basin in the Neoarchean. Post-Archean Australian Shale (PAAS)-normalized rare earth elements (REEs) plus yttrium (Y) concentrations of different BIF ores with gneissic, striated and banded structure in the Macheng deposit, show similar patterns with depletions in light rare earth elements (LREEs) and middle rare earth elements (MREEs) relative to heavy rare earth elements (HREEs) and with apparently positive La, Y and Eu anomalies. Y/Ho ratios of the gneissic, striated and banded BIF ores vary from 37 to 56. These geochemical features of the BIF ores reveal their affinity with the sea water and the presence of a high-temperature hydrothermal component, indicating that both the seawater and high temperature hydrothermal fluids derived from alteration of oceanic basalts and komatiites may contribute to formation of the Macheng BIF. Geological, mineralogical and geochemical studies of the Macheng deposit recognized two kinds of high-grade iron ores. One is massive oxidized high-grade ore (Fe2 O3 T  = 74.37–86.20 wt.%), mainly consisting of hematite with some magnetite, which shows geochemical characteristics of the gneissic, striated and banded BIF ores. The other type is magnetite high-grade ore, also massive and consisting of magnetite, with distinct characteristics in trace elements of the gneissic, striated and banded BIF ores but show similarity to those of the migmatitic iron ores with significantly negative Eu anomalies. The geochemical discrepancy or duality between the two types of high-grade ores in Macheng suggests that they formed by two different mechanisms. One is related to supergene enrichment, caused by oxidation of magnetite and the leaching of gangue minerals from BIF to form high-grade ore. The other is probably related to intensive migmatization which produced high-grade ores by altering the primary iron ores.